Proceedings of the SIGCHI Conference on Human Factors in Computing Systems Celebrating Interdependence - CHI '94 1994
DOI: 10.1145/191666.191726
|View full text |Cite
|
Sign up to set email alerts
|

Informal workplace communication

Abstract: We present new findings about the nature of informat communications, derived from a naturalistic study of people's everyday working activities. We identify why such interactions are so common, and valuable and how they are achieved in the workplace.We also address weaknesses in current systems that support such interactions remotely and identify further requirements for better support. We also discuss the implications of this work for conversational theories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(16 citation statements)
references
References 16 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…It is primarily gathered through unconscious acts as one goes about his or her workday, for example, by looking around a shared office (Fish et al, 1990, Schmidt, 2002. Thus, workplace awareness is easily gained by those in close physical proximity (Kraut et al, 1988, Whittaker et al, 1994. There exists a range of needs when it comes to workplace awareness: those who frequently collaborate require more awareness than those who do not.…”
Section: Comparison To Awareness In the Workplacementioning
confidence: 99%
See 1 more Smart Citation
“…It is primarily gathered through unconscious acts as one goes about his or her workday, for example, by looking around a shared office (Fish et al, 1990, Schmidt, 2002. Thus, workplace awareness is easily gained by those in close physical proximity (Kraut et al, 1988, Whittaker et al, 1994. There exists a range of needs when it comes to workplace awareness: those who frequently collaborate require more awareness than those who do not.…”
Section: Comparison To Awareness In the Workplacementioning
confidence: 99%
“…These range from IM, to media spaces, and a host of applications in between. Given that people are most often situated in front of a computer at work, these systems are generally designed to run on a desktop PC, but can also be found on large communal displays (Whittaker et al, 1994).…”
Section: Comparison To Awareness In the Workplacementioning
confidence: 99%
“…In nonverbal communication, Whittaker et al (Whittaker et al, 1994) also found that people who rated each other as more familiar had less formal communication and produced more interruptions; in their study, "interruption" meant to start an interaction without achieving shared attention. One way to interpret it would be that people who are more familiar with each other do not consider such interruption as it is for complete strangers.…”
Section: Familiaritymentioning
confidence: 93%
“…Familiarity within social relationships refers to the degree to which people are close to and comfortable with each other (Little, 1965). People develop different levels of familiarity with others due to frequency of interaction (Whittaker, Frohlich, & Daly-Jones, 1994): close friends, friends, acquaintances, or complete strangers. Those categories are influential factors in verbal as well as nonverbal communication.…”
Section: Familiaritymentioning
confidence: 99%
“…Workplace interaction is a phenomenon that has been a focal object of study within the areas of HCI (human-computer interaction) and CSCW (computer-supported cooperative work) for around 20 years now. During this time, the character of workplace interaction has been explored from a wide range of perspectives ranging from empirical studies of one-shot interaction (Aaronson & Carroll, 1987), serendipitous interaction (Landgren & Nuldén, 2007), casual interaction (Borning & Travers, 1991;Whittaker, Frohlich, & Daly-Jones, 1994;Whittaker, Swanson, Kucan, & Sidner, 1997), long-term social interaction (Whittaker, Jones, & Terveen, 2002), and spontaneous interaction (Lim, Zhang, Zhu, & Zheng, 2007), to studies of formal interaction (Oehlmann, Thoben, & Weber, 1997), planned interaction (Isaacs, Tang, & Morris, 1996), and structured interaction (Rogers, 1995). While this body of research has mainly focused upon the formal and informal aspects of workplace interaction, we have so far seen few studies with an explicit focus on how individuals active in these social work arrangements go about searching for each other to establish interaction, and how social factors govern this behavior.…”
Section: Introductionmentioning
confidence: 99%